Enhancing supply chain learning and innovation performance through human resource management. Issue 3 (31st August 2020) - Haq, Muhammad Zia Ul; Gu, Minhao; Huo, Baofeng
Abstract : Purpose: Despite the importance, no study exists which investigates the role of human resource (HR) in supply chain (SC) learning. This study aims to investigate the effects of high-performance human resource management (HRM) practices on different types of the SC learning (i.e. supplier, customer and internal learning) and innovation performance. Design/methodology/approach: This study applies structural equation modeling to test the conceptual model based on data collected from 213 manufacturing firms in China. Findings: The findings indicate that empowerment improves all three dimensions of SC learning, whereas training improves supplier and internal learning and teamwork is not related to any dimension of SC learning. These HRM practices also interactively influence SC learning dimensions. Moreover, customer and internal learning are directly related to innovation performance, while supplier leaning has a complementary effect with internal leaning but a substitutional effect with customer learning to innovation performance. Research limitations/implications: This study only selects training, teamwork and empowerment to manifest high-performance HRM practices. The impacts of high-performance HRM practices on different dimensions of SC learning and innovation performance are tested empirically with cross sectional-data collected only from manufacturing firms in China. Practical implications: The findings suggest that managers can promote SC learning through the empowerment and training of their employees. Moreover, managers should place more emphasis on customer and internal learning to improve innovation performance. Originality/value: Combining HRM and supply chain management (SCM) fields, this study offers a new framework to understand linkages between high-performance HRM practices, SC learning and innovation performance by using an empirical method.